Carrier-Free Immobilization of α-Galactosidase as Nano-Biocatalysts for Synthesizing Prebiotic α-Galacto-Oligosaccharides - Yan Liu (Molecules, 2021)
α-Galacto-oligosaccharides (α-GOSs) have great functions as prebiotics and therapeutics. This work established the method of batch synthesis of α-GOSs by immobilized α-galactosidase for the first time, laying a foundation for industrial applications in the future. The α-galactosidase from Aspergillus niger L63 was immobilized as cross-linked enzyme aggregates (CLEAs) nano-biocatalyst through enzyme precipitating and cross-linking steps without using carriers. Among the tested agents, the ammonium sulfate showed high precipitation efficacy and induced regular structures of α-galactosidase CLEAs (Aga-CLEAs) that had been analyzed by scanning electron microscopy and Fourier-transform infrared spectroscopy. Through optimization by response surface methodology, the ammonium sulfate-induced Aga-CLEAs achieved a high activity recovery of around 90% at 0.55 U/mL of enzymes and 36.43 mM glutaraldehyde with cross-linking for 1.71 h. Aga-CLEAs showed increased thermal stability and organic solvent tolerance. The storage ability was also improved since it maintained 74.5% activity after storing at 4 °C for three months, significantly higher than that of the free enzyme (21.6%). Moreover, Aga-CLEAs exhibited excellent reusability in the α-GOSs synthesis from galactose, retaining above 66% of enzyme activity after 10 batch reactions, with product yields all above 30%.